Research on the Fire Extinguishing Efficiency of Low-Pressure Water Mist in Urban Underground Utility Tunnel Cable Fires - Jia, Boyan; Xia, Yanwei; Ning, Zhaoyu; Li, Bin; Zhang, Guowei; Zhang, Zhiwei (Fire (Basel, Switzerland), 2023)
Low-pressure water mist fire extinguishing systems are a cost-effective and highly reliable option for fire protection. However, they have not yet seen widespread use in urban underground utility tunnels. To validate the fire extinguishing effectiveness of the system in cable fires within urban utility tunnels and to identify the key factors influencing its efficiency, a scaled-down test platform for low-pressure water mist fire extinguishing in utility tunnels was constructed, and a series of fire extinguishing tests was conducted. The test results demonstrate that low-pressure water mist can rapidly and effectively extinguish cable fires in utility tunnels, with the quickest fire extinguishing time of 7 s. Within 50 s of activating the system, the internal temperature of the tunnel can be reduced from 650 °C to 40 °C. Among the influencing factors, the pressure and nozzle flow coefficient have a significant impact on the fire extinguishing efficiency, while nozzle spacing has a relatively smaller effect. Thus, when the nozzle spacing meets the requirement of “no dead zones”, priority should be given to increasing the pressure and nozzle flow coefficient.